Dynamics of miRNA expression in urine extracellular vesicles of prostate cancer patients after radical prostatectomy - E. V. Shutko; O. E. Bryzgunova; I. A. Ostal’cev; S. V. Pak; S. E. Krasi’nikov; P. P. Laktionov; M. Yu. Konoshenko (Успехи молекулярной онкологии)
Introduction. It is known that the treatment of oncological diseases including prostate cancer (PCa) causes changes in the expression of oncogenic and oncosuppressive miRNAs. The analysis of miRNA expression dynamics can be used to predict the course of the disease and its response to therapy. However, the effect of PCa therapy on the expression of extracellular miRNAs is just beginning to be investigated.Aim. To study the expression dynamics of 14 miRNAs (miR-19b, -22-3p, -30e, -31, -92a, -125b, -144, -200b, -205, -222, -375, -378a, -425, -660) in urine extracellular vesicles of PCa patients after radical prostatectomy and to reveal prognostic miRNA ratios.Materials and methods. Urine samples of 18 donors and 18 PCa patients, obtained before radical prostatectomy, 1 week and 3 months after surgery, were examined. Extracellular vesicles were isolated by aggregation-precipitation protocol; extracellular vesicles miRNAs were isolated using fiberglass sorbents and octane acid. Data on threshold detection cycles of 14 miRNAs were obtained using reverse transcription – loop polymerase chain reaction (TaqMan).Results. It was found that prostatectomy causes a significant change in the relative expression of 44 miRNA ratios in the urine of PCa patients. Four groups of miRNA ratios can be distinguished: 1) miRNA ratios, which expression level significantly differed between donors and PCa patients before surgery and significantly changed in PCa patients 3 months after prostatectomy in the direction of the level of donors (6 pairs); 2) miRNA ratios, which expression did not significantly differ between donors and PCa patients before surgery, but significantly differed from the baseline in PCa patients and donors 3 months after prostatectomy (5 pairs); 3) miRNA ratios, based on expression ratios of which PCa patients can be divided into two or three significantly different subgroups 3 months after prostatectomy (19 pairs); 4) miRNA ratios that did not significantly change their expression after prostatectomy (30 pairs).Conclusion. Prostatectomy causes a significant change in the level of expression of miRNA in urine. 6 pairs of miRNAs, the relative expression of which after surgery significantly changed towards that of healthy donors and 19 pairs of miRNAs, according to the level of relative expression of which patients with prostate cancer were divided into two significantly different subgroups 3 months after prostatectomy, were identified based on the analysis of the dynamics of miRNA expression after prostatectomy.